A Content Analysis of Nutrition Education Curricula Used With Low-Income Audiences: Implications for Questionnaire Development. Issue 4 (July 2013) - Hernández-Garbanzo, Yenory; Griffin, Sarah; Cason, Katherine L.; Loberger, Ginger; Williams, Joel; Baker, Susan; Coffee, Aubrey; Linton, Brittney; Hall, Trisha; Hayden, Victoria
In developing recommendations for core measures/items for the evaluation of the Youth Expanded Food and Nutrition Education Program (EFNEP), three nutrition education curricula, implemented by land grant universities, were content analyzed. Selection criteria included the following: Curriculum content must include all EFNEP core content areas and must be implemented in more than one state with school children in third through fifth grades. Content analysis strategies were employed to identify and describe common areas/themes and mediators of behaviors addressed across the selected curricula. Content analysis coding was based on a list of behavioral mediators, which have empirical associations with nutrition, physical activity, and food safety. The most evident approaches identified across the three curricula were to enhance motivation, teach cognitive knowledge, and practice behavioral skills. The presence of self-regulation and environmental theory–based strategies was limited in all three curricula. In addition, multiple themes for nutrition, physical activity, and food safety were commonly addressed across curricula with multiple educational strategies. Based on these findings, recommendations for developing content appropriate measures and items for an outcome evaluation tool for Youth EFNEP are provided.